Frequency of drug-associated hyperprolactinaemia: a single-center retrospective study - Güneş, Elif; Güneş, Mutlu (The European Research Journal, 2023)
Objectives: One of the causes of hyperprolactinaemia (HP) is drug-associated HP (DAHP). In this study, it was planned to investigate the frequency of DAHP. Methods: In this study, a retrospective review of 296 individuals referred to the endocrinology outpatient clinic between June 2013 and March 2018 due to elevated prolactin (PRL) was performed. Results: Of the 296 patients included in the study, 140 (47.3%) had HP (+), 80 (27.0%) had HP (-), 27 (9.1%) had DAHP and other causes (16.6%). The causes of DAHP were as follows; sulpiride in 7 (25.9%) patients, risperidone in 6 (22.2%), amisulpride in 4 (14.8%), domperidone in 3 (11.1%), haloperidol in 2 (7.4%), paliperidone, olanzapine, escitalopram, duloxetine and otilonium bromide in one patient each. PRL levels in the DAHP group were higher than in the HP (-) group (respectively; median 114.6 [interquartile range (IQR): 144.0], median 35 [IQR 37.3], p < 0.001). Patients with DAHP had an increased frequency of symptoms compared to the HP (-) group (oligomenorrhoea; 42.3%, 16.4%, p = 0.007, galactorrhoea; 53.8%, 30.1%, p = 0.028, respectively). PRL levels were higher and the frequency of clinical signs was higher in sulpiride than risperidone (PRL; median 195.0 [IQR 99.0], median 72.0 [IQR 57.9], p = 0.022, oligomenorrhoea; 100%, 20%, p = 0.010, respectively). Conclusions: One of the 3 most common causes of patients referred for HP is DAHP and the most common cause of DAHP is anti-psychotic drugs. Sulpiride causes a higher rate of elevated PRL and frequency of clinical findings compared to other drugs.